Recent Advances in Acid-sensitive Ion Channels in Central Nervous System Diseases - Zhu, Yueqin; Hu, Xiaojie; Wang, Lili; Zhang, Jin; Pan, Xuesheng; Li, Yangyang; Cao, Rui; Li, Bowen; Lin, Huimin; Wang, Yanan; Zuo, Longquan; Huang, Yan (Current Pharmaceutical Design, 2022)
Acid-sensitive ion channels (ASICs) are cationic channels activated by extracellular protons and widely distributed in the nervous system of mammals. It belongs to the ENaC/DEG family and has four coding genes: ASIC1, ASIC2, ASIC3, and ASIC4, which encode eight subunit proteins: ASIC1a, ASIC1b, ASIC1b2, ASIC2a, ASIC2b, ASIC3, ASIC4, and ASIC5. Different subtypes of ASICs have different distributions in the central nervous system, and they play an important role in various physiological and pathological processes of the central nervous system, including synaptic plasticity, anxiety disorders, fear conditioning, depressionrelated behavior, epilepsy, Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, multiple sclerosis, malignant Glioma, pain, and others. This paper reviewed the recent studies of ASICs on the central nervous system to improve the understanding of ASICs’ physiological functions and pathological effects. This article also references studying the molecular mechanisms and therapeutic measures of nervous system-related diseases.
Keywords: central nervous system